An overview of natural coumarins (2016–2018): chemical structures and pharmacological activities - Ze-Dong Nan; Tao Liu; Jing Liu; Hui Zhang; Xiao-Yu Zhao; Yan Ge; Chong-Long Li (Results in Chemistry)
Coumarin derivatives, characterized by the core α-benzopyranone skeleton, constitute one of their most extensive classes of aromatic metabolites. These naturally occurring compounds are widely distributed in various plants and microbial fermentation products. The coumarin derivatives display diverse structural characteristics, and their molecular skeleton can give rise to several complex subclasses. Pharmacological studies have demonstrated that coumarins exhibited a broad-spectrum of biological activities. Owing to their diverse structures and potent bioactivities, these compounds have been extensively utilized in the fields of food, fragrances, and medicine. In recent years, a significant number of novel coumarin derivatives have been isolated and elucidated in nature. However, a comprehensive compilation of the corresponding scholarly literature is lacking. To address this gap, our research team recently summarized the newly discovered coumarins from plant sources between 2019 and 2024. As a complementary contribution, this review meticulously summarized the chemical structures and pharmacological activities of these coumarins. Furthermore, the structure-activity relationship (SAR) was also preliminarily discussed. In total, 156 scholarly articles encompassing 323 naturally occurring coumarin derivatives have been analyzed and documented. Through a detailed analysis and summary of the reported literature, this review lays a solid foundation for in-depth investigation and extensive application of coumarin derivatives.